(untitled) (Journal of Partial Differential Equations, 1992)
ln this paper we discuss the Dirichlet problems for a class of fully nonliucar elliptic equations F(D&sup2 u) = &#968(x, u)(&#968(x, u, &#8711u)) in Q u = &#966(x) on &#8706&#937 where F is represented by a symmetric function f(&#955_1, &#8230, &#955_n) of the eigenvalues (&#955_1, &#8230,&#955_n) of the Hessian D&sup2u. This result extends the works of Caffarelli L., Nirenberg L., Spruck L. [2] to more general cases.